Knowledge of Teachers and Students on Environmental Concerns from Elementary Eco-schools in Cuddalore District of Tamilnadu State - Sampath, K.; Sundaramoorthy, T. (JOURNAL OF INDIAN EDUCATION, 2014)
Knowledge of 110 elementary teachers and 156 students on environmental concerns was studied from 30 elementary ecoschools in Cuddalore district of Tamilnadu State from August 2006 to July 2007. A test was developed separately for teachers and students with questions under five dimensions namely biology, ecology, water resources, pollution and health & hygiene. The grand mean knowledge score of teachers recorded before interventions was 37.74 per cent and it increased considerably to 72.43 per cent after interventions. The overall mean score of teachers registered in the said five dimensions before interventions was 60.23 per cent, 63.5 per cent, 58.78 per cent, 65.70 per cent and 64.89 per cent, respectively. After interventions, the overall mean scores registered correspondingly for the said dimensions were 92.18 per cent, 89.14 per cent, 84.31 per cent, 87.12 per cent and 86.83 per cent. The grand mean knowledge score of students before interventions was 37.74 and, after interventions, it increased to 72.43 per cent. The overall mean score of the students for the said five dimensions before interventions, respectively was 37.11 per cent, 44.79 per cent, 33.20 per cent, 27.84 per cent and 39.77 per cent and the overall mean scores after interventions were 74.35 per cent, 77.28 per cent, 70.79 per cent, 66.58 per cent and 72.43 per cent. The considerable increase in the knowledge of both the teachers and students on environmental concerns was because of the introduction of the concept ecoschool and by implementing various interventions in the ecoschools.